Recombinant Tissue Plasminogen Activator (rtPA) Affects Extremity Motor Progress in Acute Ischemic Stroke Patients - Ramadhani, Dhianty; Amalia, Nuri; Putri, Mirasari (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Decreased motor function is the most common disorder caused by stroke, leading to disability. Early recanalization is the potential therapy for acute ischemic stroke, by using recombinant tissue plasminogen activator (rtPA). This study aimed to analyze the effectiveness of rtPA therapy on the motor progression of extremities in acute ischemic stroke patients.Methods: This was a retrospective cohort study using secondary data from medical records of 45 patients with acute ischemic stroke who received rtPA therapy in Al Islam Bandung Hospital, Indonesia in 2022. The limb motor progress was designated as an increase in strength motoric function skills of the left and right arms, as well as the left and right legs which were influenced by the neuroplasticity process. Marginal homogeneity test was used with significance at p<0.05.Results: Therapy of rtPA improved affected limb motor progress in patients (p=0.000). Before the administration of rtPA, all patients experienced muscle weakness. After 24 hours of rtPA therapy, patients experienced a decrease in muscle strength (9.5%), a steady state (28.6%), and increased in muscle strength (61.9%). After 72 hours, it was found that patients experienced a decrease in muscle strength (9.5%), a steady state (16.7%), and increased in muscle strength (76.2%).Conclusion: Administration of rtPA significantly affects the progress of limb motor improvement in acute ischemic stroke patients. This study supports rtPA as a? primary therapeutic option for acute ischemic stroke patients and is expected to contribute to improving the management and recovery of stroke, a critical illness associated with aging.